3‐(2‐Bromoacetamido)‐N‐(9‐ethyl‐9H)‐carbazol fluorescent probe and its application for the determination of thiophenols in rubber products by HPLC with fluorescence detection and atmospheric chemical ionization mass spectrometry identification. Issue 12 (11th May 2017) - You, Jinmao; Dou, Kun; Song, Cuihua; Li, Guoliang; Sun, Zhiwei; Zhang, Shijuan; Chen, Guang; Zhao, Xianen; Hu, Na; Zhou, Wu
Abstract : A rapid, sensitive, and selective precolumn derivatization method for the simultaneous determination of eight thiophenols using 3‐(2‐bromoacetamido)‐ N ‐(9‐ethyl‐9 H )‐carbazol as a labeling reagent by high‐performance liquid chromatography with fluorescence detection has been developed. The labeling reagent reacted with thiophenols at 50°C for 50 min in aqueous acetonitrile in the presence of borate buffer (0.10 mol/L, pH 11.2) to give high yields of thiophenol derivatives. The derivatives were identified by online postcolumn mass spectrometry. The collision‐induced dissociation spectra for thiophenol derivatives gave the corresponding specific fragment ions at m/z 251.3, 223.3, 210.9, 195.8, and 181.9. At the same time, derivatives exhibited intense fluorescence with an excitation maximum at λex = 276 nm and an emission maximum at λem = 385 nm. Excellent linear responses were observed for all analytes over the range of 0.033–6.66 μmol/L with correlation coefficients of more than 0.9997. Detection limits were in the range of 0.94–5.77 μg/L with relative standard deviations of less than 4.54%. The feasibility of derivatization allowed the development of a rapid and highly sensitive method for the quantitative analysis of trace levels of thiophenols from some rubber products. The average recoveries ( n = 3) were in the range of 87.21–101.12%.